Effect of Covid-19 Pandemic on Shrimp Farming at Navsari, Gujarat, India - Shah, Niharika P.; Ujjania , N. C.; Patel , Unnati R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The lockdown on account of the Coronavirus disease 2019 (COVID-19) adversely impacted the food production sector including aquaculture globally. Unfortunately, it coincided with the major shrimp farming season in India which contributes 60% of the national annual shrimp production hence the impact was substantial. Shrimp farmers follow the different management practices in shrimp farming operations like seed, feed, probiotics, medicine, disruptions in the supply chain, transportation, harvesting and marketing. Therefore, the objective of present study was to find out the impact of COVID-19 pandemic on shrimp farming sector in Navsari (Gujarat). These findings are depicted that management practices of the shrimp farming in study area was disturbed and huge economic losses was faced by the shrimp farmers during pandemic situations. It is suggested that technical and financial assistance for safe, sufficient and hygienic supply of seed, feed, probiotics, chemicals, medicines and probiotics by the government agencies should be ensured which help to shrimp enhance the aquaculture production and survive of shrimp farmers. The result of present study is also helpful for the government authorities to develop policies and execution of the plans during such pandemic condition for shrimp farmers that can prevent the production loss and sustain the shrimp farming industry.